A Critical Review on The Current Thought and Practice of Urban Design: New Roles in the Future - Derya Oktay (Konya Technical University Faculty of Architecture and Design, 2016)
Though urban design is historically rooted in development of cities, urban design, as a contemporary discipline, is relatively new compared to associated disciplines of architecture, urban planning, and landscape architecture. Urban design’s close connection with these allied disciplines has also been the reason for its ambiguous nature, and its muddled definition. Accordingly, it is claimed here that a reexamination of the definition, status, and role of urban design is essential for the future directions of urban design as a discipline and cities as sustainable environments. In line with this, this article provides a critical framework regarding the current understanding of the discipline of urban design which is based on form, policy and efficiency, and highlights the need for place oriented approaches performed in an interdisciplinary working framework. The paper first focuses on the meaning and significance of urban design, and discusses the problems with the manner in which urban design is conceived, practiced and researched. Second, it interrogates the contemporary framework of urban design where the notions of ‘urban’ and ‘design’ are being disconnected. Third, it examines the changing role of urban design from the traditional to the contemporary mainstream approaches. The conclusion suggests lessons in terms of understanding and framing its scale, content, professional formation, interdisciplinary nature and role in sustainable urban environments.